PENYELESAIAN TERHADAP KASUS ENCURI SARANG BURUNG WALET DI DESA PENAI BERDASARKAN HUKUM ADAT DAYAK SEBARUK - Sugianto (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
He existence of customary criminal law that applies in community life is a reflection of the daily life of the people living in the area. Each region has different customary criminal laws according to the customs that exist in that area, so that there are regions that have customary law rules that are almost the same as other regions and there are also regions where the application of customary law is completely different from other regions. The customary laws that apply in an area also depend on the customs adopted by the local community. The resolution of cases of theft can be carried out by the Traditional Leader using the customary laws that apply in the area. Customary law applies in another area, even for the same criminal offense depending on the decision made by the traditional administrator. Customary sanctions can be given to the head of a criminal, including: the obligation to pay a fine, being publicly humiliated, being expelled from the village area for perpetrators who live in the village and other customary sanctions based on the decision of the traditional leader.he traditional sanctions for stealing Sebaruk Dayak Rp.      540,000, Amaount: Rp. 50,940,000 (fifty million nine hundred and forty thousand rupiah). The Sebaruk Dayak sub-tribe community in resolving minor crimes still adheres to customary criminal law which is still trusted by the local community.